Nanofluidic Ion Transport and Energy Conversion through Ultrathin Free‐Standing Polymeric Carbon Nitride Membranes - Xiao, Kai; Giusto, Paolo; Wen, Liping; Jiang, Lei; Antonietti, Markus (Angewandte Chemie International Edition, 2018)
Ions transport through confined space with characteristic dimensions comparable to the Debye length has many applications, for example, in water desalination, dialysis, and energy conversion. However, existing 2D/3D smart porous membranes for ions transport and further applications are fragile, thermolabile, and/or difficult to scale up, limiting their practical applicability. Now, polymeric carbon nitride alternatively allows the creation of an ultrathin free‐standing carbon nitride membrane (UFSCNM), which can be fabricated by simple CVD polymerization and exhibits excellent nanofluidic ion‐transport properties. The surface‐charge‐governed ion transport also endows such UFSCNMs with the function of converting salinity gradients into electric energy. With advantages of low cost, facile fabrication, and the ease of scale up while supporting high ionic currents, UFSCNM can be considered as an alternative for energy conversion systems and new ionic devices. An ultrathin free‐standing polymeric carbon nitride membrane (UFSCNM) is fabricated by simple CVD polymerization and exhibits excellent surface‐charge‐governed ion transport properties, which endow UFSCNM with function of salinity gradient energy conversion. With advantage of low cost, facile fabrication, and ease of scaling up to support high ionic currents, UFSCNM should be an alternative for new ionic device designs.